2016
DOI: 10.5127/jep.048515
|View full text |Cite
|
Sign up to set email alerts
|

It's all about Control: Memory Bias in Anxiety is Restricted to Threat Cues that Signal Controllable Danger

Abstract: Although cognitive models of emotion propose that elevated trait anxiety may be associated with a memory bias for threatening information, evidence for such an anxiety-linked memory bias has been highly inconsistent. Given the crucial role of anxiety in preparing individuals to deal with impending danger, we hypothesized that an anxiety-linked memory bias may be restricted to cues that signal danger which can be controlled. High and low trait anxious participants performed a memory task in which three sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It appears that under some very specific conditions an anxiety-liked memory bias may be observed (e.g. Large, MacLeod, Clarke, & Notebaert, 2016;Mitte, 2008). However, our findings corroborate the general trend in the memory bias literature, suggesting there is no relationship between trait anxiety and memory bias (MacLeod & Mathews, 2004;Mitte, 2008), and extends this to memory processes that have valenced future implications.…”
Section: Discussionsupporting
confidence: 86%
“…It appears that under some very specific conditions an anxiety-liked memory bias may be observed (e.g. Large, MacLeod, Clarke, & Notebaert, 2016;Mitte, 2008). However, our findings corroborate the general trend in the memory bias literature, suggesting there is no relationship between trait anxiety and memory bias (MacLeod & Mathews, 2004;Mitte, 2008), and extends this to memory processes that have valenced future implications.…”
Section: Discussionsupporting
confidence: 86%
“…Others have proposed that anxiety-linked attentional bias may fluctuate widely from moment-to-moment (Iacoviello et al, 2014; but see Kruijt, Field, & Fox, 2016;Zvielli, Bernstein, & Koster, 2014). Moreover, recent developments have shown that biased attention may vary in response to changing contextual demands (Large, MacLeod, Clarke, & Notebaert, 2016;Notebaert et al, 2017), and in some contexts, attending to threat cues may, in spite of its effect on anxiety, also have beneficial consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Additonally, studies have demonstrated that anxiety may only enhance the retrieval of episodic threat information when there is a clear causal connection between the predictor and the aversive outcome (Toffalini et al, 2015), or when it can be controlled (Large et al, 2016). Neither these factors were present in the current design.…”
Section: Discussionmentioning
confidence: 86%